A Rare Case of Desmoplastic Mesothelioma With Good Survival Despite Lymph Node Metastasis. (11th September 2019) - Basu, Atreyee; Pass, Harvey; Zhou, Fang; Narula, Navneet; Moreira, Andre
Abstract: Introduction: Desmoplastic mesothelioma (DMM), a rare histological subtype of malignant pleural mesothelioma (MPM), is lethal and has very poor prognosis. Metastasis is commonly reported in DMM compared to other histological subtypes. Here we report a case of DMM with good survival (>1 year) despite lymph node metastasis. Case Report: A 62-year-old female with a history of smoking and possible asbestos exposure presented with cough and wheeze in 2012. Computed tomography (CT) revealed left-sided pleural plaques and multiple ground-glass pulmonary nodules. In 2017, repeat CT showed increased diffuse left nodular pleural thickening. Positron emission tomography revealed hypermetabolic, nodular pleural thickening in the hemithorax, compatible with neoplasia. Needle biopsy in January 2018 showed pleural tissue with haphazard, nodular growth of spindled mesothelial cells, suspicious for desmoplastic mesothelioma. Definitive diagnosis was not possible due to lack of fat invasion and absence of supportive evidence by immunohistochemical stains. The patient underwent pleurectomy in February 2018. On histopathology, the majority of the tumor showed a desmoplastic pattern, composed of malignant spindled cells arranged haphazardly in a dense hyalinized stroma with chronic inflammatory infiltrate. AE1/AE3, calretinin, and D2-40 immunohistochemical stains highlighted the infiltrating neoplastic cells, which were negative for WT-1. BAP-1 was retained. The pattern of immunoreactivity supported the diagnosis of DMM. The tumor also involved visceral pleura, pulmonary parenchyma, and pericardium. It invaded into fat and displayed lymphovascular invasion. A metastatic focus of DMM was present in a lymph node. The tumor was staged as pT3N1. On recent examination, the patient only had complaints of mild breathlessness and stable hydro-pneumothorax, without any other comorbidities. Conclusion: Our finding is unusual, since among the mesothelioma subtypes, DMM has the shortest survival, usually not more than 6 months. We report an extremely rare case of DMM with survival of >1 year despite invasion of lung parenchyma and lymph node metastasis.